THE MOTIVATION OF FOREIGN-EDUCATED THAIS WITH FAMILY BUSINESS BACKGROUND, IN BECOMING ENTREPRENEURS - Ruthaiyanont, Nattaphol (2011)
From interviewing 18 Thai participants (14 males and 4 females) with family business background and educated abroad. There are a few points can be concluded from the interviews. 1) They think that with their family business background make them more likely and more readily to become entrepreneurs. 2) The bond between family business and the next generation of the founder is still strong. 3) The most affected factor from the current family firm is the income of the family firm. 4) Surprisingly there are only 22% of parents who planed that their children have to take over the family firm. 5) The most common scenario that can make individuals withdrawn their intention in becoming entrepreneur is they got employed at high secure and received high salaries.